Novel Targets for Fast Antidepressant Responses: Possible Role of Endogenous Neuromodulators - Camargo, Anderson (Chronic Stress (Thousand Oaks), 2019)
The available medications for the treatment of major depressive disorder have limitations, particularly their limited efficacy, delayed therapeutic effects, and the side effects associated with treatment. These issues highlight the need for better therapeutic agents that provide more efficacious and faster effects for the management of this disorder. Ketamine, an N-methyl-D-aspartate receptor antagonist, is the prototype for novel glutamate-based antidepressants that has been shown to cause a rapid and sustained antidepressant effect even in severe refractory depressive patients. Considering the importance of these findings, several studies have been conducted to elucidate the molecular targets for ketamine’s effect. In addition, efforts are under way to characterize ketamine-like drugs. This review focuses particularly on evidence that endogenous glutamatergic neuromodulators may be able to modulate mood and to elicit fast antidepressant responses. Among these molecules, agmatine and creatine stand out as those with more published evidence of similarities with ketamine, but guanosine and ascorbic acid have also provided promising results. The possibility that these neuromodulators and ketamine have common neurobiological mechanisms, mainly the ability to activate mechanistic target of rapamycin and brain-derived neurotrophic factor signaling, and synthesis of synaptic proteins in the prefrontal cortex and/or hippocampus is presented and discussed.